When songs provide artistic value: a historical functionalism study in 1970s Indonesian popular music - Hadi, Sumasno; Sunarto, Sunarto; Cahyono, Agus; Djatiprambudi, Djuli (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2025)
The development of popular music in Indonesia as a country with rich cultural plurality, is interesting to study. The dominant study of the dangdut genre has the potential to overlook the artistic richness contained in its various musical genres. The setting of the 1970s as a historical period of global modern society that gave birth to many countercultural phenomena and leaps in communication technology in developing countries, including Indonesia, has guided the focus of our research. This research aims to answer the question of how the cluster of artistic values of 1970s Indonesian popular music in its popular songs was able to make an inspirational contribution to the development of Indonesian popular music thereafter. The choice of the conceptual foundation of art historical functionalism has led us to use an interdisciplinary research design that includes a musicological approach to analyze the form of the song, a cultural studies approach to interpret the artistic content of the music text, and a critical discourse analysis to examine the contradictions of the music discourse. From the results of the combined analysis, we found that the artistic value of 1970s Indonesian popular music stands on the foundation of artistic form supported by the three forms of songs as musical compositions, and the aesthetics of song lyrics. In addition, it was found that the cluster of artistic value that includes aesthetic value, emotional response, aesthetic value, cognitive knowledge, and historical value in 1970s Indonesian popular songs also offers artistic novelty as well as a distinctive, advanced expression impact. The findings of this study have provided additional knowledge of popular music, with an emphasis on the functionalization of the artistic value of a song in its historical setting. The findings also contribute to the need for the study of Indonesian popular music with its rich artistic content to develop an interdisciplinary approach.